The impact of a community psychological treatment programme on desistance in personality disordered sexual offenders. Issue 6 (1st November 2020) - Vieira, Claudio; Rose, Rebecca; Craissati, Jackie; Campbell, Colin
ABSTRACT: Approximately 1% of the male population acquires a sexual conviction over their lifetime with sexual recidivism rates of approximately 13% over 5 years. The effect of treatment on sexual recidivism is modest. The Challenge Project has adopted an integrative approach to the treatment of sexual offenders, combining both attachment and desistance theory. It assumes that all individuals with sexual convictions eventually desist from offending, and the intervention programme aims to maximise opportunities to achieve a prosocial life in the community. The aim of this thematic analysis was to explore the process of desistance in a sample of high-risk sexual offenders with persistent and pervasive psychological difficulties, who have been recently released to the community. Participants' experiences of their engagement in Challenge and its impact on achieving their desistance goals were captured in five key themes. As a whole, these key themes reflected the importance of high-quality relationships with professionals and support from significant others; the role of cognitive transformation and redemptive narratives in achieving key desistance goals; and managing the stigma of living with sexual convictions. These findings have potentially relevant implications for policy-making and clinical practice when working with and managing sex offenders in the community.